Facilitating the adoption of high‐throughput sequencing technologies as a plant pest diagnostic test in laboratories: A step‐by‐step description. (8th August 2022) - Lebas, Benedicte; Adams, Ian; Al Rwahnih, Maher; Baeyen, Steve; Bilodeau, Guillaume J.; Blouin, Arnaud G.; Boonham, Neil; Candresse, Thierry; Chandelier, Anne; De Jonghe, Kris; Fox, Adrian; Gaafar, Yahya Z. A.; et al.
Abstract: High‐throughput sequencing (HTS) is a powerful tool that enables the simultaneous detection and potential identification of any organisms present in a sample. The growing interest in the application of HTS technologies for routine diagnostics in plant health laboratories is triggering the development of guidelines on how to prepare laboratories for performing HTS testing. This paper describes general and technical recommendations to guide laboratories through the complex process of preparing a laboratory for HTS tests within existing quality assurance systems. From nucleic acid extractions to data analysis and interpretation, all of the steps are covered to ensure reliable and reproducible results. These guidelines are relevant for the detection and identification of any plant pest (e.g. arthropods, bacteria, fungi, nematodes, invasive plants or weeds, protozoa, viroids, viruses), and from any type of matrix (e.g. pure microbial culture, plant tissue, soil, water), regardless of the HTS technology (e.g. amplicon sequencing, shotgun sequencing) and of the application (e.g. surveillance programme, phytosanitary certification, quarantine, import control). These guidelines are written in general terms to facilitate the adoption of HTS technologies in plant pest routine diagnostics and enable broader application in all plant health fields, including research. A glossary of relevant terms is provided among the Supplementary Material. Faciliter l'adoption des technologies de séquençage à haut débit pour les tests de diagnostic effectués dans les laboratoires phytosanitaires : une description étape par étape: Le séquençage haut débit (HTS) est un outil puissant qui permet, simultanément, la détection et l'identification potentielle de tout organisme présent dans un échantillon. L'application des technologies HTS suscite un intérêt croissant dans les laboratoires phytosanitaires pour les activités de diagnostic de routine et cet intérêt a conduit à l'élaboration de directives sur la manière de préparer les laboratoires à effectuer des tests HTS. Cet article décrit les recommandations générales et techniques, élaborées afin de guider les laboratoires dans le processus complexe de se préparer aux tests HTS, dans le cadre des systèmes d'assurance qualité existants. De l'extraction des acides nucléiques à l'analyse et interprétation des données, toutes les étapes sont décrites afin de garantir des résultats fiables et reproductibles. Ces directives sont applicables pour la détection et l'identification de tout organisme nuisible aux végétaux (p. ex. arthropodes, bactéries, champignons, nématodes, plantes ou adventices envahissantes, protozoaires, viroïdes, virus), et à partir de tout type de matrice (culture microbienne pure, tissu végétal, sol, eau), quelle que soit la technologie HTS (p. ex. séquençage d'amplicons, séquençage shotgun) et l'application (p. ex. programme de surveillance, certification phytosanitaire, quarantaine, contrôle des importations). Ces directives sont rédigées avec des termes génériques afin de faciliter l'adoption des technologies HTS dans les activités de diagnostic phytosanitaire de routine et de permettre une application plus large dans tous les domaines de la santé des végétaux, y compris le domaine de la recherche. Un glossaire des termes utiles est fourni dans les documents complémentaires. Содействие внедрению технологий высокопроизводительного секвенирования в качестве диагностического теста на присутствие вредителей растений в лабораториях: пошаговое описание: Высокопроизводительное секвенирование (HTS) ‐ это мощный инструмент, позволяющий одновременно обнаруживать и потенциально идентифицировать любые организмы, присутствующие в образце. Растущий интерес к применению технологий HTS для рутинной диагностики в лабораториях, занимающихся здоровьем растений, требует разработку рекомендаций по подготовке лабораторий к проведению HTS‐тестирования. В данном документе описаны общие и технические рекомендации, которые помогут лабораториям пройти сложный процесс подготовки лаборатории к проведению HTS‐тестов в рамках существующих систем обеспечения качества. Рассматриваются все этапы для обеспечения надежных и воспроизводимых результатов, начиная с выделения нуклеиновых кислот и заканчивая анализом и интерпретацией данных. Настоящее руководство актуально для обнаружения и идентификации любого вредного организма растений (например, членистоногих, бактерий, грибов, нематод, инвазивных растений или сорняков, простейших, вироидов, вирусов) и из любого типа матрицы (например, чистая культура микроорганизмов, ткани растений, почва, вода), независимо от технологии ВПC (например, ампликонное секвенирование, дробовое секвенирование) и области применения (например, программа надзора, фитосанитарная сертификация, карантин, контроль импорта). Настоящее руководство составлено в общих терминах, чтобы облегчить внедрение технологий HTS в рутинную диагностику вредителей растений и обеспечить её более широкое применение во всех областях защиты растений, включая научные исследования. В дополнительных материалах приводится глоссарий соответствующих терминов.